Late relapse of epithelial ovarian cancer: A single institution experience - Bamias, A.; Efstathiou, E.; Vassilakopoulou, M.; Koutsoukou, V.; Papadimitriou, C.; Rodolakis, A.; Mitsibounas, D.; Vlahos, G.; Dimopoulos, M.A. (European Journal of Gynaecological Oncology, 2005)
Purpose of investigation: Late relapses are infrequent in ovarian cancer. We present the characteristics and outcome of patients who relapsed at least five years after first-line chemotherapy. Methods: Six cases were retrieved from 203 patients treated from 1994 to 1998. Results: Time to recurrence ranged from five to nine years. The initial stage was I or II in all cases, while histology was: endometrioid (4 cases), clear cell (1 case) and unspecified adenocarcinoma (1 case). Only two of five assessable patients responded to chemotherapy. Compared to earlier relapses, late relapses were characterized by earlier stages (p < 0.001), non serous histology (p = 0.010) and absence of symptoms (0% vs 46.5%, p = 0.025) at baseline. Five of 16 relapses (31%) among patients with Stage I or II were late relapses. Conclusion: Late relapses of ovarian cancer occur in early stages, where they are relatively frequent, while the chemosensitivity of the disease may be less than expected.
Keywords: Late relapse; Management; Ovarian cancer